32nd AIAA Applied Aerodynamics Conference 2014
DOI: 10.2514/6.2014-3258
|View full text |Cite
|
Sign up to set email alerts
|

Time-Spectral Rotorcraft Simulations on Overset Grids

Abstract: The Time-Spectral method is derived as a Fourier collocation scheme and applied to NASA's overset Reynolds-averaged Navier-Stokes (RANS) solver OVERFLOW. The paper outlines the Time-Spectral OVERFLOW implementation. Successful low-speed laminar plunging NACA 0012 airfoil simulations demonstrate the capability of the Time-Spectral method to resolve the highly-vortical wakes typical of more expensive three-dimensional rotorcraft configurations. Dealiasing, in the form of spectral vanishing viscosity (SVV), facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…with y = y initial + ∆y (27) Here [DD T S ] and [D T S ] are the matrices containing the time-spectral coefficients for the second and firstorder derivative terms of y, respectively, and y initial is the initial value for y. Applying the same idea used previously in the approximate factorization algorithm, ∆y can be found by taking equation (26) to the frequency domain. Therefore the system of coupled equations changes to N decoupled equations since the spectral matrices are strictly diagonal in the frequency domain.…”
Section: Iiib Second-order Derivative Problem Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…with y = y initial + ∆y (27) Here [DD T S ] and [D T S ] are the matrices containing the time-spectral coefficients for the second and firstorder derivative terms of y, respectively, and y initial is the initial value for y. Applying the same idea used previously in the approximate factorization algorithm, ∆y can be found by taking equation (26) to the frequency domain. Therefore the system of coupled equations changes to N decoupled equations since the spectral matrices are strictly diagonal in the frequency domain.…”
Section: Iiib Second-order Derivative Problem Resultsmentioning
confidence: 99%
“…Here ∆τ denotes the pseudo-time step, J refers to the Jacobian of the spatial discretization, and [D T S ] corresponds to the matrix of the time-spectral coefficients d j n as defined in equation (12). Approximate factorization is an efficient algorithm that factors the Jacobian into the following form: 4,12,25,26 [A]…”
Section: Iid Approximate Factorization Algorithmmentioning
confidence: 99%
“…The TS operator is purely imaginary so we have focused initially on undamped central difference operators; it has been shown that temporal dissipation has been successful for TS applications [44][45][46] so finitedifference-based temporal artificial dissipation will be explored as part of future work in addition to one-sided circulant differentiation operators (e.g. BDF2).…”
Section: Finite Difference Methods In Time (Fdmt)mentioning
confidence: 99%
“…In the current work, this involves wrapping the spatial residual evaluation routines (solver.rhs()) and implicit inversion operation (solver.lhs()) that can be called from the high-level Python controller. The space-time approximate factorization approach [45][46][47][55][56][57] effectively decouples the implicit solutions of the spatial and temporal systems providing a straightforward implementation of the standalone PinT module; the spatial residual is passed from the flow solver(s) to the PinT module, which performs the necessary temporal coupling (e.g.…”
Section: Vb Python-based Infrastructurementioning
confidence: 99%
See 1 more Smart Citation